Aplikasi Pencarian Sekolah Untuk Wilayah Surabaya Dengan Menggunakan GPS Berbasis Web Mobile - Brian Andreas Sutarto; Emmy Wahyuningtyas; Nia Saurina (Melek IT : Information Technology Journal, 2015)
The needs of an information is needed by everyone .Information can be obtained quickly and right through the media the internet .Education is one of the aspects that determines the quality and the achievement of a person Exactness in choosing a school is very important achievement because affect owned .Because of it , needed a search application that can provide services school .The purpose of the writing of this school is making a search application for mobile web based Surabaya. This app uses GPS (Global Positioning System) on the mobile web, users can find the location of the nearest school to the position of the user or based on the name of the school you're looking for on the mobile web. The research method used is the study of the literature, analysis of user and system analysis, designing applications using DFD, implementation and testing of the application. Search applications built this can provide information, school locations, as well as showing the route of the user's position to which it is sent. This application can be used anytime and anywhere because it can be accessed from smartphones.